FLASHCARD MATCHING GAME UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS ANAK - Sylvia, Sylvia; Harmiati (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service (PkM) was carried out with the aim of improving children's reading and writing skills in Rawakalong Village, Gunung Sindur District. The service team went into the field to provide training to children using the “flashing matching game” technique so that children were interested in engaging in learning activities. This game-based approach not only strengthens reading and writing skills in English but also improves memory skills. A major factor in the success of this PkM is the support of the local community in providing a conducive learning environment. Through this training, children can be better prepared for the challenges they face in the VUCA 4.0 era.